THE IMPACT OF MUSIC ON MOTOR DEVELOPMENT IN EARLY CHILDHOOD AT ALMA PAUD POS BAKALAN VILLAGE KALINYAMATAN DISTRICT JEPARA REGENCY - Rustandi Mulyana, Aton; Enggar Febriyanti , Monalisa (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2025)
This research aims to explore and describe in depth the influence of music on motor development in early childhood at POS PAUD ALMA Bakalan Village, Kalinyamatan, Jepara. The research method used is qualitative with participatory techniques, interviews, and content analysis of the data collected. Research participants involved PAUD teachers and early childhood children at POS PAUD ALMA. Data was collected through direct observation of children's activities when exposed to music, interviews with children and PAUD teachers, as well as content analysis of children's responses to musical experiences in the classroom. Data analysis resulted in the finding that the use of music in the context of early childhood education at ALMA PAUD POS has a positive impact on children's motoric development. Through music, children show improved gross and fine motor skills, as well as motor coordination abilities. Apart from that, music also creates a fun environment and motivates children to develop their motor skills. This research contributes to understanding the role of music as an effective learning tool and can help improve the motor skills of young children. The implications of this research can be the basis for further development in the context of early childhood education at POS PAUD and provide guidance to educational practitioners to integrate music more effectively in the learning process.